PLEONOTOMA ORIENTALIS (BIGNONIACEAE – BIGNONIEAE): EXPANDED DESCRIPTION, DISTRIBUTION AND A NEW VARIETY OF A POORLY KNOWN SPECIES - PROENÇA, C. E. B.; FARIAS-SINGER, R.; GOMES, B. M. (Edinburgh Journal of Botany, 2007)
Pleonotoma orientalis Sandwith (Bignoniaceae), a poorly known species, is lectotypified, illustrated for the first time and a distribution map is provided. Pleonotoma orientalis Sandwith var. ratteriana Proença & Farias from the Jalapão area (State of Tocantins, Central Brazil) is described and illustrated. The new variety is apparently identical to the typical variety in floral characters but distinct in its ternate-tripinnate leaves with numerous, minute, slightly thickened leaflets, and fruits with rounded or obtuse tips. The collections of this new variety increase its range c.400 km S from Northern Brazil (Maranhão and Pará) into Tocantins in Central Brazil.
Keywords: Bignoniaceae; Brazil; cerrado; Jalapão; liana; Pleonotoma; Tocantins